Pelaksanaan Perjanjian dengan Jaminan Fidusia di Kota Jambi - Nur Gita Oktaviani (CV Rewang Rencang, 2024)
Analyze the implementation of the rights and obligations of the parties who make a fiduciary agreement with W Finance Jambi City. The type of research used is in accordance with the main problem to be researched, namely empirical juridical legal research which aims to find out the laws that apply in society. The data used is primary data originating from field data obtained from respondents and informants as well as motor vehicle financing agreement document data at W Finance. The research results show that in practice the implementation of the rights and obligations of the parties in the fiduciary agreement at W Finance there are still things that are not in accordance with what was agreed, where debtors often violate these obligations and do not carry them out.